Evaluasi Pendidikan Menuju Insan Kamil Perspektif Filsafat Islam - Anwar, Saiful (Tahta Media Group, 2022)
This article aims to learn how to conduct an adequate evaluation using approaches based on Islamic philosophy. Because inconsistencies in the implementation of educational assessments can lead to less than optimal results after inspection, this requires appropriate methods for the full review. The author made this article with a library approach, collecting materials from library books, research reports, newspapers, books, research reports, theses, dissertations, and scientific journals in print and non-print media. In Islamic education, the purpose of the evaluation is to make al-Insan al-Kamil human or a complete human person. Likewise, the purpose of education is to educate students to have faith, be pious, develop a religious mentality, master science, and apply what has been learned in school to adapt to the life of the wider community. Evaluation can also provide feedback to students about their achievements and the extent of their perspectives and knowledge during the learning process. Philosophy also educates people to think, have insight, and reason broadly to view an event or problem from various perspectives, with the result being the correct answer.